Isolation of total rna at yellow stage of jatropha curcas seeds from Thailand hybrid - Terry, Madatang (Universiti Malaysia Sarawak, 2011)
Jatropha curcus seeds contain a number of secondary metabolites and polysaccharides, which make the isolation of total RNA difficult to be done. The aim for this study is to isolate high quality of RNA from yellow stage of the J. curcas seed. RNA extraction is done by using several RNA extraction protocol with modifications. Three extraction methods have been used in this research. Those methods were CTAB-LiCI I, CTAB-LiCI II and CTAB-LiCI III. From this research, seeds from the J. curcas hybrid from Thailand was taken as sample. Among these three methods, the CTAB-LiCI III was the preferred method. This method was able to yield up to 0.531 (ug/ul) with the the A260/ A280 and A260/A230 ratio ranged from 1.704 - 1.795 and 0.796 - 0.918 respectively. By using the CTAB-LiCI III protocol, the RNA was successfully isolated.